Assessment of the conformity of dairy product labels against current legislation and consumer perception of labeling (Research, Society and Development, 2021)
Labeling is the main communication link between a food product and the consumer, providing information on ingredients, presence of allergens, liquid content, enabling the comparison of products at the time of purchase. The aim of this study was to assess the conformity of dairy product labels to current legislation and to investigate consumer understanding of labeling. A cross-sectional study was carried out with the data collection of 100 dairy products through a checklist, with the answers, “compliant”, “non-compliant” and “not applicable”. A descriptive quantitative study assessed consumer perception by applying a structured questionnaire via Google Forms to 569 participants. It was found that 97% of dairy products had some kind of irregularity in relation to mandatory information. Non-conformities were observed in the indication of the country of origin, in the nutritional information, in the size of the letters, in the mode of conservation, in the declaration of allergens, and others. As for the habit of reading labels, 26.71% of the participants stated that they always read the information and 64.68% that they read it sometimes. There was a significant association between the level of education, the reading habit and the reliability of the information on the labels, evidencing that as the degree of education increases, the greater the reading habit and the confidence in the information. As it is a communication link, it is essential that the information provided is reliable and clear, because if the label is well understood, more careful food choices can be made.